Bibliometric Analysis of Genetic Variations in Schizophrenia - Azman, Norainin Sofiya; Abd Rahim, Nour El Huda; Abdull Jalil, Mohd Asyraf; A. Talib, Norlelawati; Mat Rasid, Siti Norain; Wan Salleh, Wan Muhamad Salahudin; Kaderi, Mohd Arifin; Md Rosli, Ahmad Nabil; Mohamed Bakrim, Norbaiyah (Jordan Medical Journal, 2025)
Schizophrenia is a complex neuropsychiatric disorder with significant genetic variation as an aetiology. This study aimed to explore genetic variation-related research in schizophrenia from a bibliometric perspective. A systematic search was conducted using the Scopus database to identify literature related to schizophrenia and genetic variation published between 2014 and December 17, 2023. The bibliometric data were analyzed using software such as biblioMagika®, Biblioshiny, and VOSviewer. A total of 344 publications were retrieved, showing a growth in the number of publications and citations over time, with the United States (US) having the highest number of publications at 121. Analysis of co-authorship by country also highlighted the US as the leading contributor. Michael Conlon O’Donovan was recognized as the most dominant author in the field. The Schizophrenia Research journal was found to be the most productive. Keyword analysis across different clusters identified significant research directions in schizophrenia, emphasizing treatment efficacy and the interaction of genetic and environmental factors. These findings provide a comprehensive perspective on the broader landscape of this research topic.